PERTAMAX DAN PERTALITE PADA KINERJA MESIN GASOLINE ENGINE KAPASITAS 2800 WATT - Setiyo, Edi; Sari, Dewi Puspita; Wadirin, Wadirin; Costa, Anthony; Adanta, Dendy; Marwani, Marwani; Hermawan, Rudi (Universitas Sriwijaya, 2025)
This study evaluates the impact of RON 90 and RON 92 fuels on the performance of a 4-stroke engine with a capacity of 2800 Watts. In the applied methodology, a 2800 Watt two-wheeler vehicle was used to test torque, power, and specific fuel consumption (SFC) at various engine speeds. The results show that RON 92 has better torque at 4000 RPM, while RON 90 exhibits higher torque at speeds approaching 7500 RPM. Power analysis indicates that both fuels produce the same maximum power of 8.7 HP, although it is achieved at different engine speeds. Meanwhile, in terms of SFC, RON 92 is more efficient at lower speeds, but the difference narrows at higher speeds. These findings provide insights into the performance of both types of fuel and their use in engine applications.